LEGAL FRAMEWORKS FOR PUBLIC-PRIVATE PARTNERSHIP FINANCING IN INFRASTRUCTURE DEVELOPMENT: A Comparative Study of Indonesia and the Philippines - Mubarrak, Muhammad Zaki; Amnesti, Sheila Kusuma Wardani (Fakultas Syariah, 2025)
Infrastructure development constitutes a fundamental driver of economic growth in developing countries; however, persistent fiscal constraints have compelled ASEAN states such as Indonesia and the Philippines to adopt Public–Private Partnership (PPP) schemes as alternative financing mechanisms. Despite the long-standing implementation of PPP in both jurisdictions, significant disparities in legal frameworks and institutional arrangements raise critical issues concerning regulatory efficiency, bureaucratic coordination, and legal certainty in infrastructure delivery. This study aims to comparatively examine the legal frameworks governing PPP implementation in Indonesia and the Philippines by applying the analytical standards set out in the World Bank’s Public–Private Partnership Legal Framework Reference Guide. Employing normative legal research, this study utilises statutory, conceptual, and comparative approaches to analyse PPP-related legislation, institutional governance structures, contractual arrangements, and dispute resolution mechanisms in both countries. The findings reveal that Indonesia operates under a fragmented and multi-layered regulatory regime involving numerous institutions, offering stronger legal certainty through tiered dispute resolution mechanisms, whereas the Philippines adopts a unified PPP legal code supported by a centralised PPP Center, resulting in greater procedural efficiency and investment facilitation. This article contributes to the optimal implementation of PPP through regulatory simplification and institutional centralisation for countries in the ASEAN region. Pembangunan infrastruktur merupakan prasyarat utama pertumbuhan ekonomi di negara berkembang, namun keterbatasan fiskal mendorong Indonesia dan Filipina sebagai negara ASEAN untuk mengandalkan skema Public–Private Partnership (PPP) sebagai alternatif pembiayaan yang berkelanjutan. Meskipun kedua negara telah lama menerapkan PPP, perbedaan kerangka hukum dan kelembagaan menimbulkan persoalan efektivitas, efisiensi birokrasi, serta kepastian hukum yang berdampak langsung pada keberhasilan proyek infrastruktur. Penelitian ini bertujuan membandingkan kerangka hukum PPP di Indonesia dan Filipina dengan menggunakan World Bank Public–Private Partnership Legal Framework Reference Guide untuk menilai efektivitas regulasi, struktur kelembagaan, dan mekanisme penyelesaian sengketa. Metode penelitian menggunakan pendekatan hukum normatif dengan teknik perundang-undangan dan komparatif, menganalisis peraturan PPP, struktur institusi terkait, serta pengaturan kontraktual dan penyelesaian sengketa di kedua negara. Hasil penelitian menunjukkan bahwa Indonesia memiliki kerangka regulasi yang kompleks dengan banyak institusi dan mekanisme penyelesaian sengketa berjenjang yang memberikan kepastian hukum lebih kuat, sedangkan Filipina menerapkan satu undang-undang terpadu dan satu lembaga khusus PPP Center yang menciptakan proses lebih efisien dan ramah investasi. Artikel ini berkontribusi pada bentuk optimalisasi implementasi PPP melalui penyerderhanaan regulasi dan sentralisasi kelembagaan untuk negara di kawasan ASEAN.